Tuning method for double-loop control structure for nonminimum-phase integrating systems - Han, Seer Qiu; Nandong, Jobrun (IEEE, 2015)
Nonminimum-phase processes with integrating or unstable dynamics are commonly encountered in practice. Designing high-performance PID controllers with adequate robustness for such processes is very challenging due to the limitations imposed by the unstable pole and zero. In this paper, a scheme combining the multi-scale control and double-loop structure is proposed. The scheme provides a simple way to design an effective control system for nonminimum-phase integrating processes. The basic idea is to first stabilize an integrating process using a secondary controller. Then, a main controller is tuned using a multi-scale control tuning formula to provide desired performance-robustness. The effectiveness of the proposed control scheme is compared with some of the established control strategies. © 2015 IEEE.